Goldeneye [videorecording (DVD)] - Campbell, Martin; Brosnan, Pierce; Bean, Sean; Scorupco, Izabella; Fleming, Ian, 1908-1964 (MGM Home Entertainment Inc., 1999)
When a mysterious Cossack crime lord gains control of a powerful satellite laser weapon, James Bond is sent to Russia to stop him, at all costs.